2002
DOI: 10.1029/2001gl014440
|View full text |Cite
|
Sign up to set email alerts
|

Water vapour measurements inside cirrus clouds in Northern and Southern hemispheres during INCA

Abstract: Water vapour data inside cirrus clouds from in‐situ measurements with an aircraft‐borne frost‐point hygrometer are analysed. These data have been obtained during two field campaigns, performed in the Southern and Northern hemisphere mid latitudes. There were many occurrences of ice supersaturation inside the investigated cirrus, with a higher frequency of occurrences in the Southern Hemisphere. The source of the differences in the humidity data from the two hemispheres is not clear, and it is speculated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
155
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(205 citation statements)
references
References 14 publications
49
155
1
Order By: Relevance
“…This is in good agreement with former findings of about 30 % ice supersaturation within mid-latitude cirrus clouds over the Southern Great Plains from combined Raman lidar measurements (Comstock et al, 2004) and from in situ measurements in the vicinity of Ireland (Ovarlez et al, 2002) during INCA (INter hemispheric difference in Cirrus properties from Anthropogenic emissions), respectively. The small differences in the observed fraction of supersaturated data points may be explained by an absolute error of about 10-15 % in the RHi data, resulting mainly from uncertainties in the used temperature, as well as from differences of the evolution stage of the examined cirrus cloud regimes.…”
Section: Summary and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in good agreement with former findings of about 30 % ice supersaturation within mid-latitude cirrus clouds over the Southern Great Plains from combined Raman lidar measurements (Comstock et al, 2004) and from in situ measurements in the vicinity of Ireland (Ovarlez et al, 2002) during INCA (INter hemispheric difference in Cirrus properties from Anthropogenic emissions), respectively. The small differences in the observed fraction of supersaturated data points may be explained by an absolute error of about 10-15 % in the RHi data, resulting mainly from uncertainties in the used temperature, as well as from differences of the evolution stage of the examined cirrus cloud regimes.…”
Section: Summary and Discussionsupporting
confidence: 92%
“…It has to be kept in mind that we consider only a single case study in our analysis and, as mentioned above, the comparability of this case study with former findings is limited by the evolution state of the observed cloud as well as by ambient conditions. Similar to earlier findings of a positive skewness in cold clouds (Ovarlez et al, 2002), Spichtinger et al (2004) found asymmetric RHi distributions in the upper (and colder) cloud layers based on the MOZAIC (Measurement of Ozone by Airbus In-service aircraft project) data set. They interpret their findings with the influence of vertical motion on the duration of the transition to equilibrium (Gierens, 2003) and therewith on the distribution of (super-)saturation within the cloud.…”
Section: Summary and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Both distributions are slightly asymmetric with a tail towards higher supersaturation which is more pronounced in the SHARC measurements. This agrees with results from Ovarlez et al (2002), who find similar asymmetric distributions for temperatures below -40°C.…”
Section: Comparison Of Relative Humidity In Clouds 10supporting
confidence: 82%
“…160 % (e.g. Ovarlez et al, 2002; The bias of MCH data towards higher values for the period starting in year 2000 could not be explained by physical reasons -see e.g. Lamquin et al (2012) and the discussion therein -but is related to an error in sensor handling during calibration.…”
Section: Description Of Errorsmentioning
confidence: 99%